CD5 as a prognostic marker in patients with diffuse large B-cell lymphoma: a multicenter study - Demirci, Ufuk; Kırkızlar, Hakkı Onur; Ümit, Elif G.; Gürsoy, Vildan; Pınar, İbrahim Ethem; Özkalemkaş, Fahir; Demir, Ahmet Muzaffer (Springer Science and Business Media Deutschland GmbH, 2022)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL) and comprises a heterogeneous group of disease. While classification of B-cell lymphomas has been evolving to include clonality in a specific manner, morphology, and immunohistochemistry remain the backbone. We aimed to evaluate the value of CD5 expression on disease characteristics as well as prognosis in patients with DLBCL. Data of 131 patients with DLBCL with CD5 positivity and as a comparison arm, data of 129 patients with DLBCL without CD5 positivity were evaluated. Mean age was 59 and 55.7% of the patients were male. Overall survival was 29.8 months. Poor prognostic factors including (high-LDH levels, B symptoms, low ECOG score, high R-IPI and NCCN-IPI score) were observed to be significantly related with CD5 positivity. Mean survival in CD5 positive patients were 29.8 months, which is significantly shorter than the general DLBCL survival worldwide. CD5 expression shall be evaluated in all samples of DLBCL patients due to its possible effects on outcomes. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: c-MYC; CD 5; CNS prophylaxis; Diffuse large B-cell lymphoma; Double/triple expressor